Significance of pancreatic calcification on preoperative computed tomography of intraductal papillary mucinous neoplasms. Issue 9 (18th June 2019) - Tsujimae, Masahiro; Masuda, Atsuhiro; Shiomi, Hideyuki; Toyama, Hirochika; Sofue, Keitaro; Ueshima, Eisuke; Yamakawa, Kohei; Ashina, Shigeto; Yamada, Yasutaka; Tanaka, Takeshi; Tanaka, Shunta; Nakano, Ryota; et al.
Abstract: Background and Aim: Chronic pancreatitis is a risk factor for pancreatic cancer. Pancreatic calcification is a characteristic of chronic pancreatitis; however, its significance for intraductal papillary mucinous neoplasm (IPMN) oncogenesis remains unknown. Therefore, we investigated the relationship between pancreatic calcification and invasive IPMN. Methods: This study included 157 patients who underwent resection for IPMN between April 2001 and October 2016 (intraductal papillary mucinous adenoma, n = 76; noninvasive intraductal papillary mucinous carcinoma [IPMC], n = 32; and invasive IPMC, n = 49). We divided the subjects on the basis of the presence/absence of pancreatic calcification on preoperative computed tomography (CT). The factors associated with pancreatic calcification were investigated in univariate analyses. Then, multivariate logistic regression analyses of the relationship between pancreatic calcification and invasive IPMC (after adjusting for clinical or imaging characteristics) were conducted. Results: Preoperative CT revealed pancreatic calcification in 17.2% (27/157) of the resected IPMN. In the univariate analyses, jaundice, high serum carbohydrate antigen 19‐9 levels, and invasive IPMC were significantly associated with pancreatic calcification (4/27 [14.8%] vs 4/130 [3.1%], 0.01; 12/27 [44.4%] vs 31/130 [23.8%], 0.03; and 15/27 [55.6%] vs 34/130 [26.2%], 0.001, respectively). Pancreatic calcification was significantly associated with invasive IPMC (multivariate odds ratio = 2.88, 95% confidence interval [95% CI] = 1.15–7.21, 0.03, adjusted for clinical characteristics; odds ratio = 5.50, 95% CI = 1.98–15.3, 0.001, adjusted for imaging characteristics). Conclusions: Pancreatic calcification on CT is associated with invasive IPMC. Pancreatic calcification might be a predictor of invasive IPMC.